Antagonistic activity of probiotic bacillus megaterium against streptococcus mutans - C. SUMATHI; A. NANDHINI; JAYANTHA PADMANABAN (International Journal of Pharma and Bio Sciences, 2017)
As part of a screening program aimed at the discovery of new lead compounds for the treatment of oral diseases, probiotic Bacillus megaterium isolated from fish gut was studied for its anticaries activity.Our objective is to enumerate the antibacterial effect of Bacillus megateriumagainst the dental caries causing micro organism Streptococcus mutans.Agar well diffusion to determine Zone of inhibition and MIC value was assessed through broth 2-fold macro dilution method.Our study result showed that the fish gut bacteria possess potent inhibitory activity against potentially deleterious oral bacterial pathogen, Streptococcus mutans(P <0.05). Zone of inhibition was directly proportionate toprobiotic concentration. At 2000µg of the probiotic concentration % inhibition of the oral pathogenic bacteria was more than 50%. This clearly indicates that MIC value was low against Streptococcus mutans.In conclusion the present investigation coincides with the earlier reports suggesting the potential use of probiotic Bacillus megaterium as an antimicrobial agent in treatment of Dental careis.However, detailed investigation of possible mechanism involved in anticaries activity must be probed through molecular studies.